Customer Satisfaction is Part of Industrial Business Excellence in the Industrial Revolution Era 4.0 - Muslim Muslim; M Giatman; Nurhasan Syah; Milana Milana; Wawan Purwanto; Dwi Sudarno Putra; Zikri Zikri (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
Customers as consumers of products users need to pay attention to the satisfaction they get. The study in this research is about customer satisfaction which is part of the advantages of industrial business in the era of the industrial revolution 4.0. The method used is a literature study. Data sources are articles in accredited national journals and reputable international journals. The findings show that the industrial revolution 4.0 changed the work system in an industry by utilizing the latest technology to increase competition and seek innovative strategies to achieve customer satisfaction. These findings are expected to provide information to business or corporate users, customers who use the products offered, and government agencies that participate in managing the industrial business so that they can create industrial business flows that are useful for the progress of a country's economy. Pelanggan sebagai konsumen dari pengguna produk perlu diperhatikan mengenai kepuasan yang didapatkan. Kajian dalam penelitian ini adalah mengenai kepuasan pelanggan yang merupakan bagian dari keunggulan bisnis industri pada era revolusi industri 4.0. Metode yang digunakan adalah literatur studi. Sumber data adalah artikel dalam jurnal nasional berakreditasi maupuan jurnal internasional bereputasi. Hasil temuan menunjukkan bahwa revolusi industri 4.0 merubah sistem kerja dalam suatu industri dengan memanfaatkan teknologi terkini dalam meningkatkan persaingan dan mencari strategi yang inovatif untuk mencapai kepuasan pelanggan. Temuan ini diharapkan menjadi informasi kepada pengguna bisnis atau perusahaan, pelanggan pengguna produk yang ditawarkan serta lembaga pemerintahan yang ikut mengelola bisnis industri sehingga bisa menciptakan arus bisnis industri yang berguna untuk kemajuan perekonomian suatu negara.